PERANCANGAN KAPAL CONTAINER 250 TEUS RUTE PELAYARAN TANJUNG PRIOK-BELAWAN DENGAN KECEPATAN 14 KNOT - Bobby Alexander Sulihdiono (2020)
Container vessels are vessels specifically used to transport containers. Medan City has a strategy of city development policy that focuses on improving residential facilities and infrastructure through the construction of road network. This development requires a large amount of asphalt that needs to be brought from other regions. Asphalt is imported from DKI Jakarta and West Java area. 250 TEUS container ship design is planned to carry asphalt bags from the port of Tanjung Priok and carry semi-finished rubber from the port of Belawan. The container ship design uses a two-vessel comparison method and trial and error method.